After Empire : Scott, Naipaul, Rushdie - Gorra, Michael Edward (Chicago, Ill. : University of Chicago Press, 1997)
In After Empire Michael Gorra explores how three novelists of empire, Paul Scott, V.S. Naipaul, and Salman Rushdie, have charted the perpetually drawn and perpetually blurred boundaries of identity left in the wake of British imperialism. Arguing against a model of cultural identity based on race, Gorra begins with Scott's portrait, in The Raj Quartet, of the character Hari Kumar, a seeming oxymoron, an "English boy with a dark brown skin," whose very existence undercuts the belief in an absolute distinction between England and India.
The situation: Paul Scott and the Raj Quartet -- V.S. Naipaul: in his father's house -- The novel in an age of ideology: on the form of midnight's children -- Appendix to ch. 3. "Burn the books and trust the book": the satanic verses, February 1989.
Includes bibliographical references and index.
Print version record.
eBooks on EBSCOhost
Keywords: Scott, Paul, -- 1920-1978.; Naipaul, V. S. -- 1932-2018 -- Knowledge -- India; Rushdie, Salman; Naipaul, V. S. -- 1932-2018; Midnight's children (Rushdie, Salman); Raj quartet (Scott, Paul); English fiction -- 20th century -- History and criticism; National characteristics, British, in literature; Indic fiction (English) -- History and criticism; Anglo-Indian fiction -- History and criticism; Decolonization in literature; Imperialism in literature; India -- In literature; Roman anglais -- 20e siècle -- Histoire et critique; Britanniques dans la littérature.; Roman de l'Inde (anglais) -- Histoire et critique; Roman anglo-indien -- Histoire et critique; Décolonisation dans la littérature.; Impérialisme dans la littérature.; LITERARY CRITICISM -- European -- English, Irish, Scottish, Welsh; Anglo-Indian fiction; Decolonization in literature; English fiction; Imperialism in literature; Indic fiction (English); Literature; National characteristics, British, in literature; India; 1900-1999; Criticism, interpretation, etc